2013
DOI: 10.1093/eurheartj/eht200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renal denervation with a standard irrigated cardiac ablation catheter on blood pressure and renal function in patients with chronic kidney disease and resistant hypertension

Abstract: The procedure using SICAC seemed to be feasible, effective, and safe resulting in a better control of BP, a short-term increase in estimated glomerular filtration rate, and reduced albuminuria. Although encouraging, our data are preliminary and need to be validated in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 33 publications
7
72
2
1
Order By: Relevance
“…As we described previously [5,6], the reduction in office BP was evident from the 1st month until one year after RSD in refractory hypertensive patients. A recent study in animals showed the pathology of radiofrequencyderived RSD during the time and provided important knowledge of the mechanisms resulting in sustained BP reduction, and reported that the nerve damage post radiofrequency ablation was greatest at 7 days, with maximum functional nerve damage sustained ≤30 days.…”
supporting
confidence: 69%
“…As we described previously [5,6], the reduction in office BP was evident from the 1st month until one year after RSD in refractory hypertensive patients. A recent study in animals showed the pathology of radiofrequencyderived RSD during the time and provided important knowledge of the mechanisms resulting in sustained BP reduction, and reported that the nerve damage post radiofrequency ablation was greatest at 7 days, with maximum functional nerve damage sustained ≤30 days.…”
supporting
confidence: 69%
“…We calculated the estimated glomerular filtration rate (eGFR) using the CKD-EPI equation, which is known to perform better for a larger range of GFR values [5]. The adopted protocol [6] for denervation involved the delivery of a higher number of ablative lesions per artery than in previous studies [7,8] and an irrigated catheter with the more wide contact area. Sympathetic activation is a trademark of the essential hypertensive state happening early in the clinical course of the disease, even in the controlled patients [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the procedure, the anatomy of the renal arteries was checked by angiography to assess whether there were any complications during the procedure. [18] The procedure was performed without any complications, and the patients remained clinically stable and awoke fully from sedation. Intravenous protamine was infused at the end of the procedure, and manual compression of the femoral artery was performed with a mean time of 15 min, followed by the compressive dressing.…”
Section: Renal Sympathetic Denervationmentioning
confidence: 95%
“…Some small focal irregularities of the renal arteries that were present during the procedure (possibly due to minor spasm or oedema) were no longer seen postoperatively. [18] At the sixth month after the procedure all the patients from RSD group underwent a Doppler scan of renal arteries without any evidence of stenosis or flow limitation. [18] Effects on blood pressure…”
Section: Safety Evaluation Of Rsdmentioning
confidence: 99%